Ministry of Education: Re-engaging for success - Trinidad and Tobago. Ministry of Education (Ministry of Education, Trinidad and Tobago, 2022)
This report notes that in July, 2022, Cabinet approved a range of operational recommendations in the Revised Operational Plan for 26 Secondary Schools. Following this, in December, 2022, Cabinet approved the implementation of a Remediation Program in 80 primary schools, with additional measures to be implemented in the 26 secondary schools of focus. Thus, in academic year 2022/23, and continuing, 106 schools are the objects of intense focus by the MOE. Among the criteria used for selection are: Primary Schools - 1. The total number and/or percentage of students who scored less than 30% in SEA 2021 and the number/percentage from the previous two years; 2. The need for support with regards to the leadership and governance structure at the school; 3. Student academic achievement; 4. Shortcomings in completion of the curriculum and method of curriculum delivery; 5. High student absenteeism/truancy; 6. High levels of referral re: student indiscipline; 7. High levels of critical incidents; 8. Socio-economic challenges; and 9. Lack of parental involvement and supervision. Secondary Schools - 1. Percentage of Form 1 intake for 2020/21 academic year scoring 30% and less; 2. The percentage of students achieving 5 or more CSEC subjects inclusive of Mathematics and English A (CSEC Threshold) over the period 2019-2021; and 3. The value-added measure: Estimating Students Progress Towards 5 subjects for the period 2017-2019. This newly developed measure takes into consideration SEA scores and students CSEC grades five years later.
Ministry of Education Press Conference
Keywords: Education, remediation